Aberrant CD Expression in Acute Myeloid Leukaemia- A Cohort Study in Sri Lanka - Kariyawasan, C. C.; Balasuriya, B. L. T.; Ranatunga, S. A. C. D. (Disease and Health Research - New Insights Vol. 1, 2024)
Background: Acute leukaemia is defined as the presence of over 20% of blasts cells in the blood or bone marrow. Acute myeloid leukaemia (AML) and acute lymphoblastic leukaemia (ALL) are the 2 main types. Acute myeloid leukaemia is a cancer of the myeloid lineage of blood cells and it is the commonest form of acute leukaemia in adults with a median age of 65 years. AMLs have characteristic morphological findings and molecular features with different surface and cytoplasmic cluster of differentiation (CD) markers. These CD markers are determined by immunophenotyping/flow cytometry on leukocytes which helps with accurate diagnosis and reproducibility of AMLs. Flow cytometry plays an important role in the diagnosis, sub classification and monitoring of patients with AML. AML generally shows aberrant CD expression or co- expression in relation to normal myeloid cells. Objective of the Study: Objective of the Study was to evaluate the frequency and the pattern of aberrant CD expression in AML patients referred to a tertiary care hospital in Sri Lanka in comparison to other published data. There was no comparative data available in respect of Sri Lanka. Materials and Methods: A retrospective descriptive study including 26 cases of AML diagnosed over a period of 12 months were analyzed. Diagnosis of AML was made by morphology of peripheral blood, bone marrow, trephine biopsies, Sudan Black B stain and the immunophenotypic analysis by multiparameter flow cytometry on bone marrow aspirates or peripheral blood. The markers used in flow cytometry were CD 45, CD34, CD19, CD7, smCD3, cyCD3, cyMPO, cyCD79a, CD20, CD15, CD10, CD5, HLADR, CD64, CD13, CD117, CD33, and CD14. The identification of blasts cells was performed using forward scatter (FSC) versus side scatter (SSC) parameters and CD45 intensity versus SSC dot plots. Results: Diagnosed AMLs were morphologically classified according to the French-American-British (FAB) Classification (FAB Subtypes). Among the 26 AML patients, 15 cases (57.69%) had the conventional CD antigen expressions of myeloid lineage. Other 11 cases (42.3%) were AML with aberrant expression of CD markers. Aberrancies of cyCD3 and CD7 were observed in 54.5% and 45.4% AML cases, respectively. smCD3 in 1 case out of 11 aberrant AML cases. Co expression of T lymphoid markers with myeloid markers occurred in 23% cases in our study. CD13 was not expressed in 1 case out of 5 AML- M4 cases and 1 case out of 7 AML- M1. CD33 was not expressed in 1 case out of 2 AML -M0 cases. Conclusion: We conclude that aberrant expression of CD markers is seen in a significant population of AMLs. cyCD 3, CD7 and smCD 3 were the aberrant markers present in our study population with cyCD3 showing highest frequency.